A Seventh-Order Scheme for Computing the Generalized Drazin Inverse - Dilan Ahmed; Mudhafar Hama; Karwan Hama Faraj Jwamer; Stanford Shateyi (Mathematics, 2019)
One of the most important generalized inverses is the Drazin inverse, which is defined for square matrices having an index. The objective of this work is to investigate and present a computational tool in the form of an iterative method for computing this task. This scheme reaches the seventh rate of convergence as long as a suitable initial matrix is chosen and by employing only five matrix products per cycle. After some analytical discussions, several tests are provided to show the efficiency of the presented formulation.